Design considerations of the European DEMO's IR-interferometer/polarimeter based on TRAVIS simulations. (1st April 2022) - Brunner, K.J.; Marushchenko, N.; Turkin, Y.; Biel, W.; Knauer, J.; Hirsch, M.; Wolf, R.C.
Abstract: Interferometry is the primary density control diagnostic for large-scale fusion devices, including ITER and DEMO. In this paper we present a ray tracing simulation based on TRAVIS accounting for relativistic effects. The study shows that measurements will over-estimate the plasma density by as much as 20°. In addition, we present a measurement geometry, which will enable vertical position control during the plasma's ramp-up phase when gap-reflectometers and neutron cameras are still blind.